2013
DOI: 10.1111/jac.12031
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Cell‐Wall Components as Influenced in the First Phase of Salt Stress in Three Maize (Zea mays L.) Hybrids Differing in Salt Resistance

Abstract: The leaf cell wall (CW) chemical composition of three maize (Zea mays L.) hybrids (salt-resistant SR 03 and SR 12, salt-sensitive Pioneer 3906) was investigated in the first phase of salt stress (100 mM NaCl) compared with the control (1 mM NaCl) treatment to investigate whether changes in CW composition were responsible for shoot growth reduction. Salt treatment caused a strong inhibition in shoot growth with a concomitant increase in the ratio between CW dry mass (DM) and shoot fresh mass (FM) and a decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 50 publications
(70 reference statements)
1
34
0
1
Order By: Relevance
“…2,3b,c), and also of bands assigned to cellulose. A similar reduction in cellulose content promoted by saline conditions has been previously reported in tobacco cells adapted to grow in 0.428 M NaCl, in which the proportion of cellulose was only 50 % that of unadapted cells (Iraki et al 1989), as well as in cell walls of cotton seedlings (Zhong and Läuchli 1993) and maize leaves (Uddin et al 2013) under saline stress. The change of trend in the cellulose content observed when calluses are subjected to concentrations of NaCl well below the I 50 (in this case, 50 mM, whereas the I 50 is 160 mM) might be attributed to a subtoxic effect promoted by the saline conditions.…”
Section: Assay Of the Cellulose Contentsupporting
confidence: 83%
See 1 more Smart Citation
“…2,3b,c), and also of bands assigned to cellulose. A similar reduction in cellulose content promoted by saline conditions has been previously reported in tobacco cells adapted to grow in 0.428 M NaCl, in which the proportion of cellulose was only 50 % that of unadapted cells (Iraki et al 1989), as well as in cell walls of cotton seedlings (Zhong and Läuchli 1993) and maize leaves (Uddin et al 2013) under saline stress. The change of trend in the cellulose content observed when calluses are subjected to concentrations of NaCl well below the I 50 (in this case, 50 mM, whereas the I 50 is 160 mM) might be attributed to a subtoxic effect promoted by the saline conditions.…”
Section: Assay Of the Cellulose Contentsupporting
confidence: 83%
“…This is correlated to the more intense labeling with JIM7 observed in 200 mM NaCl-treated calluses, but it is not necessary an objection to the observed intense labeling with JIM5 in the same calluses. In fact, cellulose-impoverished cell walls as those of tomato dichlobenil-habituated are characterized by a general increment of pectic polysaccharides (both esterified and non-esterified) (Wells et al 1994), and those of different maize hybrids subjected to salt stress (Uddin et al 2013). …”
Section: Immunolocation Of Cell Wall Proteins and Pectinsmentioning
confidence: 99%
“…Expansins, wall-loosening enzymes located within the apoplast of the elongation zone of leaves (Cosgrove 2000), regulate cell elongation. Their function is acid dependent and may contribute to cell wall loosening below pH 5 (Cosgrove 2000;Uddin et al 2013). Pitann et al (2009a) observed a reduction in the β-expansin protein in a salt-sensitive maize hybrid exposed to salt stress, while the salt-resistant hybrid was less affected.…”
Section: Germination and Plant Growthmentioning
confidence: 99%
“…For example, six isoforms of expansins were investigated in a resistant and a tolerant maize cultivar which differed in upregulation or downregulation (Geilfus et al 2010). The alteration/adaptation in cell wall chemical composition may also contribute to salt resistance in maize, as a low accumulation of non-methylated uronic acid in leaf cell walls may contribute to salt resistance in the first phase of salt stress (Uddin et al 2013).…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…Thus it appeared that BARI Maize 5 and BARI Maize 7 performed relatively better under salt stress compared to Mosaic maize line and Plain maize line. Several investigations have shown that salt stress imposed by NaCl causes a persistent decrease of the elongation rate of maize leaves (Chazen et al, 1995;Neumann, 1993), thereby reducing shoot growth (Uddin et al, 2014;Uddin et al, 2013;Hatzig et al, 2010). Salt stress (10 dS m -1 ) significantly (P ≤ 5.0%) increased shoot Na + content both in young and old shoot of the four maize genotypes (Fig.…”
Section: Resultsmentioning
confidence: 86%